Imperial Southwest in P. A. Krushevan's Travelogue “What is Russia?” - P. V. Alekseev (Научный диалог)
This article examines P. A. Krushevan's travelogue “What is Russia?” (1896) within the context of imperial perceptions of the Southwestern fringes of the Russian Empire. The relevance of this study lies in the necessity to explore the mechanisms of imperial policy and nationalist discourse in travel writing as instruments for shaping ideological views on space and population. The paper investigates Krushevan's journey, his concept of unifying nationalism, and the imagological strategies employed in his descriptions of Ukrainians, Poles, Jews, and other ethnic groups. It establishes that the author places particular emphasis on Kyiv as a sacred center of Russian statehood and a symbolic space where the question of acceptable boundaries for national amalgamation is addressed. The study demonstrates how, through his travel narrative, Krushevan projects an envisioned image of imperial unity by utilizing the mechanism of imagined borders. It explores the connection between his route and the ideological concepts of Russian civilizational mission, where territorial integrity is seen as a guarantee of national unity. Key elements of imperial discourse are identified, including notions of an internal “East,” national hierarchies, and strategies of exclusion. Analyzing the travelogue provides deeper insights into how images of “the familiar” and “the other” were constructed within the imperial consciousness and what rhetorical techniques were employed to legitimize them.